2019
DOI: 10.1016/j.jsps.2019.02.008
|View full text |Cite
|
Sign up to set email alerts
|

The use of chitosan-coated flexible liposomes as a remarkable carrier to enhance the antitumor efficacy of 5-fluorouracil against colorectal cancer

Abstract: Surface-coated nanocarriers have been extensively used to enhance the delivery of anticancer drugs and improve their therapeutic index. In this study, chitosan (CS)-coated flexible liposomes (chitosomes) containing 5-fluorouracil (5-FU) were designed and characterized for use as a novel approach to target colon cancer cells. 5-FU-loaded flexible liposomes (F1, F2, and F3) and 5-FU-loaded chitosomes (F4, F5, and F6) were prepared using film hydration and electrostatic deposition techniques, respectively. The pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(47 citation statements)
references
References 38 publications
2
44
1
Order By: Relevance
“…The effect of the surfactant concentration on the particle size could be attributed to the reduction of the surface tension of the media at higher surfactant concentration and so arrangement of the phospholipid in small vesicles as previously reported [5]. The decrease in the EE of the prepared vesicles that was observed at higher surfactant concentration could be attributed to the formation of micelles molecules that compete for the drug molecules with the lipid vesicles.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…The effect of the surfactant concentration on the particle size could be attributed to the reduction of the surface tension of the media at higher surfactant concentration and so arrangement of the phospholipid in small vesicles as previously reported [5]. The decrease in the EE of the prepared vesicles that was observed at higher surfactant concentration could be attributed to the formation of micelles molecules that compete for the drug molecules with the lipid vesicles.…”
Section: Discussionsupporting
confidence: 69%
“…The in vitro release of RSV from the prepared liposomal NPs, chitosomes nano-formulation and pure drug suspension was studied as previously reported [5]. A quantity of each preparation containing 9 mg of drug was placed in a firmly sealed dialysis bag (Sigma-Aldrich Inc.) of a molecular weight cut-off 14 kDa.…”
Section: In Vitro Release Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The PDI value for particles with a 20:1 ratio decreased from 0.213 to 0.159 compared with bare liposomes. These results can be explained by the electrostatic interaction between the liposomes, which have a strong negative surface charge, and glycol chitosan that has oppositely charged surface amine groups [21] (Figure 1). The size of the particles increased exponentially at a higher GC rate, which indicates that the degree of electrostatic interaction between the liposomes and GC must be well controlled to maintain the stability of the particles.…”
Section: Resultsmentioning
confidence: 99%
“…The resulting alteration of the surface charge can be used to monitor the efficiency of chitosan coating. In an in vitro drug release assay, A. Alomrani et al [ 65 ] revealed that chitosan-coated liposomes could more effectively reduce 5-fluorouracil leakage than conventional liposomes, and chitosan coating increased the cytotoxicity of 5-fluorouracil toward CRC cells (HT-29) in a sustained manner. These discoveries suggest that LCLs are promising DDSs with the potency of increasing the stability, safety, and efficacy of the delivered drug.…”
Section: Current Lipid-based Nanoplatformsmentioning
confidence: 99%